Effects of caseous lymphadenitis agent (corynebacterium pseudotuberculosis) isolated from superficial abscesses of sheep on oxidative stress factors: Oxidative Stress in Sheep with Caseous Lymphadenitis - Polat, E; Kaya, E; Karagülle, B; Akin, H (Journal of the Hellenic Veterinary Medical Society, 2023)
In this study, it was aimed to determine the incidence of Corynebacterium pseudotuberculosis (C. pseudotuberculosis) in caseous lymphadenitis cases in superficial lymph nodes of sheep and to evaluate its effect on oxidative stress factors. Thus, it was aimed to determine the early diagnosability of superficial and visceral caseous lymphadenitis cases and to prevent the spread of diseases and related economic losses. A total of 103 sheep, 50 of which were healthy and 53 of which had caseous lymphadenitis, were evaluated in the study. Microbiological examinations were performed by taking 3-5 ml of pyogenic aspirate from the superficial lymph nodes of sheep with caseous lymphadenitis. Blood samples were taken from sheep with C. pseudotuberculosis isolated in microbiological examinations and the levels of oxidative stress factors were determined. C. pseudotuberculosis was isolated in 23 of the pyogenic aspirates of 53 sheep with caseous lymphadenitis. When sheep isolated from C. pseudotuberculosis were compared with healthy sheep, it was determined that there was a statistically significant decrease in the levels of antioxidant molecules such as GSH-pX (14.62%), GSH (23.81%), SOD (4.70%), CAT (22.23%) (p˂0.001). The level of toxic malondialdehyde (MDA) (18.62%), the end product of lipid peroxidation, was found to be statistically significantly increased in sheep isolated from C. pseudotuberculosis (p˂0.001). As a result, it was determined that oxidative stress factors showed statistically significant variability in cases of superficial caseous lymphadenitis (caused by C.pseudotuberculosis). For this reason, by determining the levels of oxidative stress factors in suspected herds, it was possible to make early diagnosis of the superficial and visceral forms of caseous lymphadenitis, and a basis was established for future studies.